2023
DOI: 10.1021/acs.jproteome.3c00130
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Profiling of Lysine Acylome in Sepsis-Induced Liver Injury

Ann-Yae Na,
So Young Choi,
Sanjita Paudel
et al.

Abstract: Sepsis is one of the life-threatening diseases worldwide. Despite the continuous progress in medicine, the specific mechanism of sepsis remains unclear. A key strategy of pathogens is to use post-translational modification to modulate host factors critical for infection. We employed global immunoprecipitation technology for lysine acetylation (Kac), succinylation (Ksu), and malonylation (Kmal) for the first global lysine acylation (Kacy) analysis in a cecum ligation and puncture (CLP) model in mouse. This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…34 Fang et al reported 3731 Kac sites on 1421 cellular proteins in porcine reproductive and respiratory syndrome virus-infected pulmonary alveolar macrophages and hepatocytes, which are the primary cells of the liver; thus, they have become the subject of global acetylome studies over the past decade. 13,35,36 In this study, we identified 2186 Kac sites in 925 ImKC proteins, which were characterized via GO enrichment analysis of Kac proteins. Kac in ImKC is well- enriched in the ribosome, spliceosome, and carbon metabolism categories, as reported in previous studies, by global acetylome DAVID analysis (Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Fang et al reported 3731 Kac sites on 1421 cellular proteins in porcine reproductive and respiratory syndrome virus-infected pulmonary alveolar macrophages and hepatocytes, which are the primary cells of the liver; thus, they have become the subject of global acetylome studies over the past decade. 13,35,36 In this study, we identified 2186 Kac sites in 925 ImKC proteins, which were characterized via GO enrichment analysis of Kac proteins. Kac in ImKC is well- enriched in the ribosome, spliceosome, and carbon metabolism categories, as reported in previous studies, by global acetylome DAVID analysis (Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale proteomic approaches in mouse liver mitochondria have been performed, 11,12 and studies have been conducted in hepatocytes, HepG2 cells, and AML-12 cells. 13,14 Although various global acetylome studies have been performed on liver and liver-derived cells, no studies involving KCs have been performed.…”
Section: Introductionmentioning
confidence: 99%